Analysis Of Yusuf Al-Qaradhawi's Fatwa On Boycott Of Israeli Products From An Islamic Economic Perspective - Paisal Rahmat Matondang; Afriadi Sanusi; Nur Mutiah; Marlian Arif Nasution (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2026)
This study analyzes Yusuf Al-Qaradhawi's fatwa on boycotting Israeli products from an Islamic economic perspective. This fatwa calls for a boycott of products in response to political policies that harm Muslims, especially in the Palestinian-Israeli conflict. The study aims to understand the sharia legal basis underlying the fatwa, as well as its implications for consumption behavior and economic ethics in Islam. Through a qualitative descriptive analysis method, this study explores Al-Qaradhawi's argument that boycott is a legitimate form of economic jihad in order to defend the rights of Muslims, as long as it does not cause harm to the boycotters. The results show that this fatwa is based on the principles of justice, social responsibility and economic solidarity in Islam. Boycotts are seen as a means to protect the interests of the Ummah, reduce economic dependence on countries hostile to Islam, and encourage the growth of local industries. The findings also highlight the challenges and potential economic impact of implementing boycotts in the era of globalization.